Can students learn about local wisdom in their area only? (Development of elementary school IPAS teaching materials) - Benyamin Regi; Yufrinalis, Marianus; Yohanes Ehe Lawotan; Yonas Klemens Gregorius Dori Gobang (Jurnal Pendidikan Indonesia, 2025)
This research is motivated by the learning situation in the classroom which is still conventional and fixated on the textbooks provided by the school. Teachers have not been creative and innovative in designing teaching materials so that they do not improve student learning outcomes. The purpose of this research is to increase teachers' understanding and creativity in developing science and technology teaching materials based on Guti Nale local wisdom in Lembata Regency. The development research procedure uses the ADDIE development model. The subjects in this study are 22 students in grade IV of SDK Aliuroba in Lembata Regency. Data collection was carried out through document studies, observations, questionnaire distribution and interviews with teachers who developed teaching materials. Data analysis is carried out qualitatively, starting from data collection, data reduction, data presentation and drawing conclusions. The results of the study show that teachers are able to develop elementary science teaching materials based on local wisdom "Guti Nale" in Lembata Regency. The results of this study also have implications for the development of students' understanding and learning outcomes and increase the spirit of loving local traditions.